Flanders and the Anglo-Norman world, 1066-1216 - Oksanen, Eljas (Cambridge : Cambridge University Press, 2012)
"The union of Normandy and England in 1066 recast the political map of western Europe and marked the beginning of a new era in the region's international history. This book is a groundbreaking investigation of the relations and exchanges between the county of Flanders and the Anglo-Norman realm. Among other important themes, it examines Anglo-Flemish diplomatic treaties and fiefs, international aristocratic culture, the growth of overseas commerce, immigration into England and the construction of new social and national identities. The century and a half between the conquest of England by the duke of Normandy and the conquest of Normandy by the king of France witnessed major revolutions in European society, politics and culture. This study explores the history of England, northern France and southern Low Countries in relation to each other during this period, giving fresh perspectives to the historical development of north-western Europe in the Central Middle Ages"--
Machine generated contents note: Introduction; 1. Power and politics in Flanders and the Anglo-Norman Regnum; 2. Military treaties and diplomatic culture; 3. Anglo-Flemish diplomacy: context and mechanisms; 4. Tournament in Anglo-Flemish society; 5. Politics of cross-Channel commerce; 6. Flemish immigration to England; 7. Social identity and the image of Flemings in England; Conclusion; Appendices; Bibliography.
Includes bibliographical references.
Keywords: History -- Europe -- General; England -- Relations -- Flanders; Europe -- History -- 476-1492.; Flanders -- History -- To 1500.; Flanders -- Relations -- England; Great Britain -- History -- Norman period, 1066-1154.